2020
DOI: 10.1038/s41598-020-60427-2
|View full text |Cite
|
Sign up to set email alerts
|

Topical recombinant human Nerve growth factor (rh-NGF) is neuroprotective to retinal ganglion cells by targeting secondary degeneration

Abstract: Optic neuropathy is a major cause of irreversible blindness worldwide, and no effective treatment is currently available. Secondary degeneration is believed to be the major contributor to retinal ganglion cell (RGc) death, the endpoint of optic neuropathy. partial optic nerve transection (pont) is an established model of optic neuropathy. Although the mechanisms of primary and secondary degeneration have been delineated in this model, until now how this is influenced by therapy is not well-understood. in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Therefore, effective treatment should include a drug that selectively activates the neuroprotective TrkA or inhibits the proapoptotic p75 NTR [52,54]. On the other hand, Guo et al [55] showed that topical administration of recombinant human NGF (rh-NGF) does exert significant neuro-Ophthalmic Res 2021;64:345-355 DOI: 10.1159/000514441 protection in animal optic neuropathy models. The described mechanism involves inhibition of the secondary neurodegenerative processes [55].…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…Therefore, effective treatment should include a drug that selectively activates the neuroprotective TrkA or inhibits the proapoptotic p75 NTR [52,54]. On the other hand, Guo et al [55] showed that topical administration of recombinant human NGF (rh-NGF) does exert significant neuro-Ophthalmic Res 2021;64:345-355 DOI: 10.1159/000514441 protection in animal optic neuropathy models. The described mechanism involves inhibition of the secondary neurodegenerative processes [55].…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…NGF administration reduced apoptosis of RGC in vivo and thus increased the RGC population in the lower retina, which is primarily affected by this disease. In addition, NGF inhibits astrocytic activity in the optic nerve and promotes axonal survival after pONT [13]. Visual acuity and electrofunctional parameter improvements were detected after topical treatment with NGF in an AMD patient after 3 months [14], and in five children with optic glioma and optic nerve atrophy [15].…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 94%
“…76 More recently, topical administration of rh-NGF was found to prevent RGC apoptosis, promote axonal survival, and inhibit astrocyte-driven optic nerve degeneration. 77 Similarly, intraocular NGF administration significantly reduced functional retinal ganglion cell damage in a rat model of retinal ischemia. 78 The neuroprotective effects of NGF were corroborated in subsequent animal studies of glaucoma.…”
Section: Optic Nerve Diseasementioning
confidence: 94%